2016
DOI: 10.1098/rstb.2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Why developmental psychology is incomplete without comparative and cross-cultural perspectives

Abstract: One contribution of 16 to a theme issue 'Understanding self and other: from origins to disorders'. As a discipline, developmental psychology has a long history of relying on animal models and data collected among distinct cultural groups to enrich and inform theories of the ways social and cognitive processes unfold through the lifespan. However, approaches that draw together developmental, cross-cultural and comparative perspectives remain rare. The need for such an approach is reflected in the papers by Heye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 106 publications
(117 reference statements)
2
87
0
2
Order By: Relevance
“…Previous research has shown that whereas some cultural differences in social behaviour emerge early in development (Legare & Harris, 2016;Nielsen & Haun, 2016;Over & Uskul, 2016), certain aspects of intergroup cognition appear to show cultural invariance (Dunham, Baron, & Banaji, 2006;Dunham, Srinivasan, Dotsch, & Barner, 2014). Understanding the nature and extent of cultural variation must be a priority for developmental research, especially research centering on the construction and transmission of social information, such as that relating to groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that whereas some cultural differences in social behaviour emerge early in development (Legare & Harris, 2016;Nielsen & Haun, 2016;Over & Uskul, 2016), certain aspects of intergroup cognition appear to show cultural invariance (Dunham, Baron, & Banaji, 2006;Dunham, Srinivasan, Dotsch, & Barner, 2014). Understanding the nature and extent of cultural variation must be a priority for developmental research, especially research centering on the construction and transmission of social information, such as that relating to groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently there is not enough data from other cultures to begin to grasp the effects of such variation, and the field will benefit significantly from more crosscultural comparisons [70]. Note also that so-called 'SES effects' are not solely reducible to cultural influences; they are also linked to a host of environmental factors (e.g., diet [71] and activity [72]) that affect brain development [73].…”
Section: Relationships Between Language and The Environmentmentioning
confidence: 99%
“…The commentary by Nielsen & Haun [21] draws together the approaches mentioned here. It emphasizes the importance of adopting a comparative and cross-cultural approach to understanding development in particular, and social cognition more generally.…”
Section: Origins: the Evolution And Development Of Social Cognitionmentioning
confidence: 99%